Effects of environmental cocaine concentrations on the skeletal muscle of the European eel (Anguilla anguilla) - Anna Capaldo; Flaminia Gay; Marilena Lepretti; Gaetana Paolella; Stefania Martucciello; Lillà Lionetti; Ivana Caputo; Vincenza Laforgia (Science of The Total Environment, 2018)
The presence of illicit drugs in the aquatic environment represents a newpotential risk for aquatic organisms, due to their constant exposure to substanceswith strong pharmacological activity. Currently, little is known about the ecological effects of illicit drugs. The aimof this study was to evaluate the influence of environmental concentrations of cocaine, an illicit drug widespread in surface waters, on the skeletal muscle of the European eel (Anguilla anguilla). The skeletal muscle of silver eels exposed to 20 ng L−1 of cocaine for 50 days were compared to control, vehicle control and two post-exposure recovery groups (3 and 10 days after interruption of cocaine). The eels general health, the morphology of the skeletal muscle and several parameters indicative of the skeletal muscle physiology were evaluated, namely the muscle whole protein profile, marker of the expression levels of the main muscle proteins; cytochrome oxidase activity, markers of oxidative metabolism; caspase-3, marker of apoptosis activation; serum levels of creatine kinase, lactate dehydrogenase and aspartate aminotransferase, markers of skeletal muscle damages. Cocaine-exposed eels appeared hyperactive but they showed the same general health status as the other groups. In contrast, their skeletal muscle showed evidence of serious injury, including muscle breakdown and swelling, similar to that typical of rhabdomyolysis. These changes were still present 10 days after the interruption of cocaine exposure. In fact,with the exception of the expression levels of the main muscle proteins, which remained unchanged, all the other parameters examined showed alterations that persisted for at least 10 days after the interruption of cocaine exposure. This study shows that even low environmental concentrations of cocaine cause severe damage to the morphology and physiology of the skeletal muscle of the silver eel, confirming the harmful impact of cocaine in the environment that potentially affects the survival of this species.